2019
DOI: 10.1097/ana.0000000000000593
|View full text |Cite
|
Sign up to set email alerts
|

Transient Neurological Events After Surgery for Pediatric Moyamoya Disease: A Retrospective Study of Postoperative Sedation Practices

Abstract: Background: Moyamoya disease is a cerebrovascular disease characterized by bilateral stenosis of the intracranial internal carotid arteries and an abnormal collateral vascular network at the base of the brain. Transient neurological events (TNEs), which are episodes of neurological dysfunction lasting <24 hours, are associated with stroke in pediatric patients with Moyamoya disease. Perioperative agitation often occurs in pediatric patients. We hypothesized that anesthetic technique and postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The primary outcome was the occurrence of TNEs within the first 24 hours postoperatively. TNEs were defined as episodes of neurological dysfunction lasting <24 hours as previously described 11,12. The evaluation period for TNEs was limited to the first 24 hours postoperatively as all patients spent at least one 24-hour period in the ICU under the same rigorous ICU-specific nursing protocols with hourly neurological exams and Doppler graft evaluations each shift.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was the occurrence of TNEs within the first 24 hours postoperatively. TNEs were defined as episodes of neurological dysfunction lasting <24 hours as previously described 11,12. The evaluation period for TNEs was limited to the first 24 hours postoperatively as all patients spent at least one 24-hour period in the ICU under the same rigorous ICU-specific nursing protocols with hourly neurological exams and Doppler graft evaluations each shift.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has confirmed that EEG is useful for evaluating transient neurological events in MMD to distinguish seizures and epileptiform changes [ 150 ]. Additionally, postoperative transient neurological dysfunction resulting from transient cortical depression often occurs in MMD [ 151 ]. This can be detected by EEG, as low amplitude arrhythmic slowing in the corresponding hemisphere [ 152 ].…”
Section: Neuroimaging Evaluationsmentioning
confidence: 99%
“…Pain control and sedation are optimized. 18,29,35 At our institution, we titrate analgesia based on the Face, Legs, Activity, Cry, Consolability Behavioral Pain Scale for nonverbal patients or the Wong-Baker FACES Pain Rating Scale for all others. For patients requiring sedation, a State Behavioral Scale goal is set daily, and sedatives are titrated to that goal.…”
Section: Postoperativementioning
confidence: 99%
“…13 Most published perioperative management protocols focus on the intraoperative course. [13][14][15][16][17][18][19][20][21][22] Patients are commonly admitted to the pediatric intensive care unit (PICU) after anesthesia, but little has been published to guide postoperative intensive care management, such as specifics of blood pressure management, hemodynamic and neurologic monitoring, laboratory parameters, and criteria for deescalation. Our pediatric neurocritical care team sought to create a multidisciplinary periprocedural evidence-and consensus-based care pathway for high-risk pediatric patients with moyamoya arteriopathy undergoing anesthesia for any reason to decrease the incidence of periprocedural stroke or transient ischemic attack (TIA).…”
mentioning
confidence: 99%